2010
DOI: 10.1103/physreva.82.023404
|View full text |Cite|
|
Sign up to set email alerts
|

Low-energyK-shell Compton scattering

Abstract: We calculate the photon energy distribution and the total cross section for the Compton scattering on the K electrons for the case when the photon wave length is much smaller than the size of the K shell. We show that at the energies of the order of the binding energy I of the K electron most part of the spectrum is governed by the low-energy behavior. The total cross section has a local maximum at the energies (1.5-2)I , reaching the values of the order 1 barn. At higher photon energies the spectrum curves ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…Some studies have indicated that the RIA approach can be realized by making leading order approximations for more advanced methods [15,51,52]. In the past few years, several approaches beyond the IA formulation have been investigated [7,[51][52][53][54][55][56][57][58][59][60]. These works, which mainly employed low-energy theorems and S-matrix formulation, revealed many remarkable and nontrivial aspects of Compton scatterings and have gained a significant interests in interdisciplinary studies.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have indicated that the RIA approach can be realized by making leading order approximations for more advanced methods [15,51,52]. In the past few years, several approaches beyond the IA formulation have been investigated [7,[51][52][53][54][55][56][57][58][59][60]. These works, which mainly employed low-energy theorems and S-matrix formulation, revealed many remarkable and nontrivial aspects of Compton scatterings and have gained a significant interests in interdisciplinary studies.…”
Section: Discussionmentioning
confidence: 99%
“…In the present work, we have studied the energy spectrum of Compton scattering through FEA and RIA formulations. However, in the past few years, several approaches beyond FEA and RIA have already been investigated recently [53][54][55][56][57][58][59]. These researches, which mainly employing low-energy theorems and S-matrix formulation, have revealed many nontrivial properties of Compton scatterings and have attracted lots of interests in interdisciplinary studies.…”
Section: Discussionmentioning
confidence: 99%
“…This problem was more recently tackled by Drukarev et al [12], who also used the work of Gavrila, and also an approximation to numerically avoid the infra-red divergence. Their total Compton cross-section does fall at low energies, however, their highest-energy cross-sections at 100 eV are mismatched by an order-of-magnitude against those in Ref.…”
mentioning
confidence: 99%
“…The sum of the individual cross-sections σR(ω) is also shown as the solid line, and is seen to monotonically decrease. Raman (σ R ) Raman 1s-3d (σ r;3d ) Raman 1s-2s (σ r;2s ) 1s-2s (Sadeghpour) photon frequencies ω ′ [12],…”
mentioning
confidence: 99%
See 1 more Smart Citation